Effects of Work-Family Conflict on job satisfaction of academicians in private universities in Bangladesh: a Structural Equation Modelling approach - Rahman, Mohammad Mizanur; Abdul, Mohani; Mansor, Zuraina; Ali, Noor Azman; Samuel, Adedeji Babatunji; Uddin, Mohammad Jamal; Aishatu Ogiri, Ibrahim; Rahaman, Md. Saidur (Penerbit Akademia Baru, 2018)
The current study attempts to examine the effects of Work-Family Conflict (W-FC) on job satisfaction of academicians. The researchers gathered the data using convenience sampling technique administered on 211 respondents who were academicians of private universities in Bangladesh. Various statistical measures such as descriptive statistics and zero-order correlation were used to explore the relationships between WFC, FWC and job satisfaction. In addition, the Structural Equation Modeling (SEM) technique was adopted to test the effects of WFC and FWC on job satisfaction. Consequently, in terms of the effects, WFC has significant negative effect on job satisfaction while FWC does not show any significant effect on job satisfaction. This study recommends that higher authorities of universities in Bangladesh should take necessary initiatives to minimize the W-FC of academicians in order to ensure their job satisfaction.